2012
DOI: 10.1007/s12033-012-9606-8
|View full text |Cite
|
Sign up to set email alerts
|

The K-Segments of the Wheat Dehydrin DHN-5 are Essential for the Protection of Lactate Dehydrogenase and β-Glucosidase Activities In Vitro

Abstract: The wheat dehydrin DHN-5 has been previously shown to exhibit heat protecting effect on enzymatic activities. In order to understand the molecular mechanism by which DHN-5 exerts its protective function, we performed an approach to dissect the functional domains of DHN-5 responsible for this feature. In two distinct enzymatic assays, we found that the truncated forms of DHN-5 containing only one K- or two K-segments are able to protect albeit to less extent than the wild type protein, lactate dehydrogenase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 26 publications
2
87
0
1
Order By: Relevance
“…The presence of exogenous proline in culture medium reinforces this fact. Eventually and due to its multi-functionality, the ability to chelate salt and its molecular chaperone effect (Brini et al 2010;Drira et al 2013Drira et al , 2015, DHN-5 represents a real solution to minimize the negative effects of salt stress. Indeed, it is likely that it modulates mechanisms involved in salt tolerance, such as proline metabolism and ROS scavenging system.…”
Section: Proline Amount and Chlorophyll Level Account For Acquisitionmentioning
confidence: 99%
“…The presence of exogenous proline in culture medium reinforces this fact. Eventually and due to its multi-functionality, the ability to chelate salt and its molecular chaperone effect (Brini et al 2010;Drira et al 2013Drira et al , 2015, DHN-5 represents a real solution to minimize the negative effects of salt stress. Indeed, it is likely that it modulates mechanisms involved in salt tolerance, such as proline metabolism and ROS scavenging system.…”
Section: Proline Amount and Chlorophyll Level Account For Acquisitionmentioning
confidence: 99%
“…Based on these observations, the authors suggested that the K-segments must be important for the recovery of LDH activity. A recently published paper on wheat (Triticum aestivum) DHN-5, also using deletion mutants, suggested that the K-segments are critical for dehydrin's protective functions (Drira et al, 2013).…”
Section: Enzymatic Cryoprotectionmentioning
confidence: 99%
“…Less conserved motifs, the ø-segments are usually rich in polar amino acids and lay interspersed between K-segments [24] [51]. The K-segments of the wheat dehydrin DHN-5 are essential for the protection of lactate dehydrogenase and β-glucosidase activities in vitro [52]. The presence and arrangement of these different motifs in a single polypeptide allow the classification of group 2 LEA proteins into five subgroups [53] [54].…”
Section: Lea Groupmentioning
confidence: 99%